Targeting MRP2 in HepG2 Cells Using the CRISPR-Cas9 System to Reverse Oxaliplatin Resistance - Zou, Ying (Auckland University of Technology, 2019)
As a third-generation platinum-based anticancer drug, oxaliplatin is critically important in the treatment of hepatocellular carcinoma (HCC), colorectal (CRC) and other GI cancers, improving disease- and progression-free survival when added to combination chemotherapy regimens. However, due to the intrinsic and acquired drug resistance, its clinical efficacy is limited, which is still a challenging problem for successful chemotherapy of hepatocellular carcinoma. Previously studies indicated that membrane transporter MRP2-mediated drug efflux effects determine the cellular accumulation and cytotoxicity of platinum drugs. Therefore, we hypothesized that the resistance effect could be reversed by perturbation of ABCC2 gene (encoding MRP2). The CRISPR-Cas 9 system, as a gene editing tool, can be used to knock out the gene of interest. MRP2 by manipulating genes. We hypothesized that the CRISPR-Cas9 technology can be applied for knocking-out ABCC2 in an in vitro cell model overexpression MRP2 (i.e. HepG2 cell line). The HepG2 cells were transfected with ABCC2 guide-RNA/CAS9 protein ribonucleoprotein complexes through liposome-mediated delivery. The efficiency of ABCC2 gene disruption was then assessed using the T7 endonuclease I based method. The accumulation of a specific ABCC2 substrate 5(6)-carboxy-2',7'-dichlorofluorescein (CDCF) was determined in the gRNA/Cas9 transfected and wild type HepG2 cells by using flow cytometeric analysis. MTT ((3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) assay was undertaken to determine oxaliplatin sensitivity, and concentration-dependent cytotoxic effects of oxaliplatin was compared between gRNA/Cas9 transfected and wild type HepG2 cells. Our current results reveal the feasibility of application of the liposome delivered CRISPR-Cas9 system to knock out ABCC2 gene in HepG2 cell line. Two sgRNAs were tested in this thesis, one of which showed that the target gene could not be effectively knocked out for unknown reasons. Fortunately, the second gRNA plays a role in disabling target genes with a genomic cleavage efficiency of 25% in HepG2 cells. Increased model MRP2 substrate (CDCF) accumulation and oxaliplatin cytotoxicity was observed for ABCC2-knockout HepG2 cells compared to control wild type. These results demonstrate that the on-target genomic editing in cell line treated by CRISPR-Cas9, and silencing ABCC2 gene by CRISPR-Cas9 does reduced the function of MRP2 protein. This thesis provide prove-of principle in vitro evidence supporting a novel therapeutic strategy that knockout of ABCC2 gene can decrease MRP2 function and increase oxaliplatin chemosensitivity in hepatocellular carcinoma.
Keywords: MRP2; HepG2; CRISPR-Cas9; Oxaliplatin